The Role of ESG Disclosure and Net Zero Emission Strategy in Reducing Cost of Capital - Khasanah , Ulfatul (CV. Civiliza Publishing, 2025)
Sustainability issues remain a major focus in global business practices. This has encouraged many companies to implement environmental, social, and governance (ESG) disclosure. The government also supports this by setting a net-zero emission target. This minimizes environmental risks and increases investor confidence. This study aims to analyze the effect of ESG Disclosure and net-zero emissions on the cost of capital. The study was conducted on companies in the energy and raw materials sector listed on the Indonesia Stock Exchange. A quantitative approach was used with a casual design. The sample size for this study was 10 companies selected through purposive sampling. The data used were secondary data, processed using multiple linear regression with SPSS software. The analysis results indicate that ESG Disclosure has a significant negative effect on the cost of capital. Net-zero emissions have been shown to significantly reduce the cost of capital. These findings reinforce the view that ESG Disclosure and a net-zero emission strategy can provide positive signals to investors, reduce financing risks, and increase corporate legitimacy among stakeholders. The practical implications of this study's findings can serve as a foundation for company management to improve the quality of ESG reporting and achieve Net Zero Emission targets, for investors to consider sustainability aspects in risk assessments, and for regulators to formulate more detailed sustainability reporting policies.